How to Put It Plainly? Findings From Two Randomized Controlled Studies on Writing Plain Language Summaries for Psychological Meta-Analyses - Kerwer, Martin; Stoll, Marlene; Jonas, Mark; Benz, Gesa; Chasiotis, Anita (Frontiers in Psychology, 2021)
Plain language summaries (PLS) aim to communicate research findings to laypersons in an easily understandable manner. Despite the societal relevance of making psychological research findings available to the public, our empirical knowledge on how to write PLS of psychology studies is still scarce. In this article, we present two experimental studies investigating six characteristics of PLS for psychological meta-analyses. We specifically focused on approaches for (1) handling technical terms, (2) communicating the quality of evidence by explaining the methodological approach of meta-analyses, (3) explaining how synthesized studies operationalized their research questions, (4) handling statistical terms, (5) structuring PLS, and (6) explaining complex meta-analytic designs. To develop empirically validated guidelines on writing PLS, two randomized controlled studies including large samples stratified for education status, age and gender (NStudy1 = 2,288 and NStudy2 = 2,211) were conducted. Eight PLS of meta-analyses from different areas of psychology were investigated as study materials. Main outcome variables were user experience (i.e., perceived accessibility, perceived understanding, perceived empowerment) and knowledge acquisition, as well as understanding and knowledge of the quality of evidence. Overall, our hypotheses were partially confirmed, with our results underlining, among other things, the importance of explaining or replacing content-related technical terms (i.e., theoretical concepts) and indicating the detrimental effects of providing too many details on statistical concepts on user experience. Drawing on these and further findings, we derive five empirically well-founded rules on the lay-friendly communication of meta-analytic research findings in psychology. Implications for PLS authors and future research on PLS are discussed.